Electron cyclotron resonance heating beam broadening in the edge turbulent plasma of fusion machines. (23rd February 2015) - Sysoeva, E.V.; da Silva, F.; Gusakov, E.Z.; Heuraux, S.; Popov, A.Yu.
Abstract: Two analytical models for the ordinary mode propagating through a turbulent inhomogeneous edge plasma layer are developed based on the eikonal perturbation method and weak turbulence theory approach. Simple analytical expression for a diffusion-like angular beam width variation is obtained by both methods in the case of long scale density perturbations. The predictions for the spatial beam width are benchmarked against timeaveraged results coming from the 2D Maxwell's equations solver for different turbulence k -spectra and plasma conditions. The strong (more than twofold) increase of the microwave beam angular and spatial width after crossing the turbulent edge is predicted at realistic parameters for ECRH experiments at ITER.